Pengembangan Aplikasi Gim Edukasi Pengenalan Buah-buahan Berbasis Android - Ahmad Syahroni Deniwinata (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to develop an educational game as an alternative medium in learning English based on Android, entitled